Podchody k fiziceskoj podgotovke futbolistov, vystupajušcich v tret'em divizione pervenstva Rossii - Volkov, V. V.; Dolmatova, T. V.; Mirošnikov, A. B.; Selujanov, V. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The problem of physical preparation of amateur footballers which combine work at facilities with participation in the games of the third division of the Championship of Russia is the minimum amount of free time for training. In this regard, it is necessary to solve the task of maintaining and enhancing physical capabilities with minimal time. To implement this idea,the training programs presented in the training manuals on football are not suitable, since they are designed to train professional athletes. Therefore, there is a need to develop approaches to the physical training of amateur footballers in conditions of a limited amount of training time.